Zinc Application Enhances Biological Yield and Alters Nutrient Uptake by Cotton (Gossypium hirsutum L.). Issue 3 (4th February 2019) - Ahmed, Niaz; Abid, Muhammad; Ali, Muhammad Arif; Masood, Sajid; Rashid, Abdul; Noreen, Sibgha; Hussain, Shahid
ABSTRACT: Zinc (Zn) deficiency is often associated with calcareous soils throughout the world, whereas application of Zn not only enhances biological yield but exhibits significant interactions with nutrients. Hence, a two-year field experiment was performed in 2004 and 2005 to assess the crop Zn requirements as well as nutrient interactions in cotton. The present study followed a randomized complete block design with five Zn levels: 0.0, 5.0, 7.5, 10.0, and 12.5 kg Zn as ZnSO4 .7H2 O. The biological yield of cotton increased progressively with increasing Zn rates. In general, cotton yield was higher in 2005 over 2004. Interestingly, Zn fertilization resulted in increased accumulation of nitrogen (N), potassium (K), boron (B), and Zn, whereas decreased the phosphorus (P), calcium (Ca), magnesium (Mg), iron (Fe), copper (Cu), and manganese (Mn) (p ≤ 0.05) uptake by cotton. The enhanced macronutrients accumulation in cotton by Zn application improved the cotton yield. In conclusion, biological yield and nutrient composition of the cotton plant are greatly influenced by Zn supply under irrigated environments.